Add-In basierte Softwaretools zur stochastischen Unternehmensbewertung? Spreadsheet basierte Monte-Carlo-Simulation und Risikoanalyse bei den vier marktführenden Softwarepaketen im Vergleich - Martin Klein (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Rechnungswesen und Prüfungswesen, 2010)
– Valuation always has to deal with uncertainty. The paper provides an overview and illustration of how Monte Carlo simulation can enrich the due diligence process. Therefore ; the four major software offerings on the market today are reviewed. The investigation addresses different characteristics of the packages such as abilities to create distributions ; resources available for learning the software ; and analytical capabilities.
Keywords: C80; G17; G32; G34; 650; valuation; due diligence; Monte Carlo Method; Crystal Ball; @Risk; ModelRisk; Risk Solver; probability management; scenario analysis; risk analysis; due diligence; Unternehmensbewertung; Monte-Carlo-Simulation; Simulationssoftware; Szenarioanalyse; Sensitivitätsanalyse; Risikoanalyse; Due Diligence